2000
DOI: 10.2307/3236780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface disturbance and light level on seedling emergence in a Japanese secondary deciduous forest

Abstract: Abstract. The effects of soil surface disturbance and light level on seedling emergence were examined by creating experimental conditions differing in soil surface treatment and light level in a temperate deciduous broadleaved secondary forest in central Japan. The results of MANOVA showed that soil surface disturbance exerted a favourable influence upon the seedling emergence of many species. Effect of soil disturbance on total density and number of emerged species was greater than that of a high light level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 29 publications
2
21
2
Order By: Relevance
“…This suggests soil surface disturbance does not improve seed-soil contact or microenvironmental conditions around the seeds (Hadas, 1982). Although contrary to results of a number of studies showing that soil surface texture can have a large impact on emergence (Eckert et al, 1986;Hamrick & Lee, 1987;Young et al, 1990;Kobayashi & Kamitani, 2000), this is perhaps not surprising. A winter beneath several meters of snow probably promotes sufficient contact, and, because germination takes place during snowmelt, water availability is probably not the problem as it would be later in the season (Gutterman, 1993;Kigel, 1995).…”
Section: Soil Surface Effects F Emergencecontrasting
confidence: 52%
“…This suggests soil surface disturbance does not improve seed-soil contact or microenvironmental conditions around the seeds (Hadas, 1982). Although contrary to results of a number of studies showing that soil surface texture can have a large impact on emergence (Eckert et al, 1986;Hamrick & Lee, 1987;Young et al, 1990;Kobayashi & Kamitani, 2000), this is perhaps not surprising. A winter beneath several meters of snow probably promotes sufficient contact, and, because germination takes place during snowmelt, water availability is probably not the problem as it would be later in the season (Gutterman, 1993;Kigel, 1995).…”
Section: Soil Surface Effects F Emergencecontrasting
confidence: 52%
“…Although light availability is clearly important, many studies have shown that also other factors play important role in regeneration success (e.g. Kuuluvainen 1994, Gray and Spies 1997, Kuuluvainen and Juntunen 1998, Wright et al 1998, Kobayashi and Kamitani 2000 and the actual effects of light still require further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Light conditions are important for the establishment of many tree species (e.g., Kobayashi and Kamitani 2000). Species typical for early stages of succession are usually r-strategists, and they are more sensitive for competition of species typical for older stages (Odum 1969).…”
Section: Discussionmentioning
confidence: 99%